DAMPAK KEBIJAKAN LOKAL TERHADAP EFISIENSI DAN EFEKTIVITAS PENATAUSAHAAN KEUANGAN DAERAH PADA PEMERINTAHAN KABUPATEN KETAPANG - ME, edi karnadi (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This research writing have aim to know and analyse the excess and lack of local policy for orderer of Financially in this time executed in Regency of Ketapang and also to analyse the local policy execution impact to efficiency and effectiveness Financially Region at Commanding Regency of Ketapang. Data Type used is data qualitative from Government of Ketapang Regency, steming from direct interconnected informano by orderer of finance in Regency of Ketapang and also other source consisted by the letter, law and regulation, book, and bound up official documents. Result of Research that local policy in Regency of Ketapang most is not effective and inefficient, but that way domestic minister policy also there are some which is not effective Keywords : Local Policy, Efficiency, Effectiveness, Area Finance